The Effect of the Flipped Classroom Model on Second-Semester Students’ Reading Comprehension in the Reading for Enjoyment Course at UHN I Gusti Bagus Sugriwa Denpasar - Anak Agung Ira Anjani; Ni Wayan Satri Adnyani; Putu Santi Oktarina (Educational Journal, 2026)
This study sought to examine the effect of the Flipped Classroom Model on the reading comprehension of second-semester students enrolled in the Reading for Enjoyment course at UHN I Gusti Bagus Sugriwa Denpasar. A quantitative research design was applied, employing a quasi-experimental approach. The study involved participants who were from the English Language Education Department, comprising a total of 34 students who were allocated into experimental and control groups. A convenience sampling technique was chosen for the sample. The research instrument was a reading comprehension test comprising 25 multiple-choice questions. The analysis of data was conducted through descriptive statistics and Analysis of Covariance (ANCOVA), utilizing pre-test scores as the covariate to account for initial disparities in reading ability. The results indicated that the Flipped Classroom Model did not have a significant effect on students' reading comprehension achievement. The findings revealed that scores obtained in the pre-test had a substantial effect on students' post-test achievement, F (1,31) = 10.978, p = .002. However, when pre-test scores were accounted for, no statistically significant difference was observed between the experimental and control groups, F (1,31) = 0.191, p = .665. The experimental group achieved a higher mean score (M = 82.92) compared to the control group (M = 81.62), although the difference was not statistically significant. Therefore, the Flipped Classroom Model did not lead to notable enhancement in students’ reading comprehension achievement compared to the traditional teaching method. Nevertheless, it may be considered a potential alternative strategy for teaching reading comprehension as it encourages students to prepare and engage with reading materials before classroom activities.